Plasma exchange therapy for a severe relapse of Devic's disease in a pregnant woman: A case report and concise review (2016)
Neuromyelitis optica (NMO) or Devic's disease is an autoimmune inflammatory demyelinating condition affecting the central nervous system (CNS). It was initially believed to be a variant of multiple sclerosis (MS). However, the discovery of NMO-IgG anti-AQP4 antibodies marked an objective distinction between these conditions. Treatment of acute attacks is generally based on pulsed steroids, followed by long-term immunosuppression with azathioprine, oral steroids, and rituximab as first-line therapies. Plasma exchange therapy is indicated for steroid-resistant relapses. We describe a case report of a pregnant woman with a severe relapse of Devic's disease, initially misdiagnosed as MS, unresponsive to pulsed steroids, and who underwent plasma exchange therapy safely, with excellent clinical response and with no adverse outcome for the fetus. © 2016 Elsevier B.V.